2013
DOI: 10.1016/j.ijpharm.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidative stress on expression and function of human and rat organic anion transporting polypeptides in the liver

Abstract: 17Reactive oxygen species (ROS) have physiological function and involve alteration of 18 physical state. However, it is not clear effect of oxidative stress on pharmacokinetics. Organic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Human OATP1B1 is expressed on the basement outer membrane of the hepatocyte membrane, and has a homologous transporter oatp1b2 in rat liver cells. There is a high degree of homology between human and rat liver transporters and studies in rat can be references for studies in human 27,28 . However, the alteration of OATPs expression did not completely parallel between human and rat primary hepatocytes, and there is no strict one-to-one relationship between human OATPs genes and rodent OATPs genes 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Human OATP1B1 is expressed on the basement outer membrane of the hepatocyte membrane, and has a homologous transporter oatp1b2 in rat liver cells. There is a high degree of homology between human and rat liver transporters and studies in rat can be references for studies in human 27,28 . However, the alteration of OATPs expression did not completely parallel between human and rat primary hepatocytes, and there is no strict one-to-one relationship between human OATPs genes and rodent OATPs genes 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Although mRNA levels of Oatp1a1, Oatp1b2 and Oatp2b1 were decreased at 6 h after intestinal I/R, these protein levels in intestinal I/R rats were same as those in sham-operated rats. The decreases in Oatps expression levels by ROS were recovered with time, though mRNA levels were still decreased (25). These findings also suggested that ROS mainly caused the decreases in Oatp1a1 and Oatp2b1 expression levels after intestinal I/R.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, the production of ROS during ischemia and early stage of reperfusion may cause the alteration of Oatp1a1 and Oatp2b1 protein expression, as well as those of mRNA. Indeed, ROS are known to decrease Oatps expression (25). Although mRNA levels of Oatp1a1, Oatp1b2 and Oatp2b1 were decreased at 6 h after intestinal I/R, these protein levels in intestinal I/R rats were same as those in sham-operated rats.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, other factors that can down-regulate Oatp1a1 expression include hyperthyroidism (Engels et al, 2015), high-cholesterol diet (Kawase et al, 2017), caloric restriction (Kulkarni et al, 2013), dysbiosis (Kuno et al, 2016), rheumatoid arthritis (Lin et al, 2017), intestinal ischemia-reperfusion (Maruyama et al, 2013), diabetes (Shuboni-Mulligan et al, 2019), hepatic metastatic tumors (Sun et al, 2006), oxidative stress (Tsujimoto et al, 2013) and polycystic kidney disease (Bezençon et al, 2019). From the available reports, almost all pathological changes down-regulate Oatp1a1 expression.…”
Section: Oatp1a1 In Pathological Statementioning
confidence: 99%